The Model And Evaluation Of Swaying Arm To The Torso Torque Of Humanoid Robot During Walking - Razali, Muhammad Razmi (2016)
The humanoid robot stand is the posture where the net torque and force generated by gravity is zero. Thus, the balance of the robot body is produced and keeping the vertical axis equilibrium behaviour. However, during the robot walking, the torque of the torso is disrupted by the internal forces of lower limbs motion. The increase of torso torque will then cause the robot to stumble or fell down. The swing arm motion is a natural phenomenon that realized in the humanoid robot walking. The swaying arm angle range is introduced in this study to utilize the humanoid robot arm motion during walking. The main idea of this technique is the employment of the right shoulder and left shoulder joint angle to reduce the torque at the torso in the vertical direction. The torso torque is computed using a method which utilized the servo torque of right hip, left hip, right shoulder and left shoulder. The torso torque, τ